Analysis and Modeling of Converter with PWM Output for Two-Phase Motor Applications - Zaskalicky, P.; Dobrucky, B.; Prazenica, M. (Elektronika ir Elektrotechnika, 2014)
This paper presents a steady state analysis of two-phase voltage-source converters with pulse width modulation (PWM) and output voltage control for small two-phase motor drives. The mathematical models of the different converter connections are built on condition of assumption of idealized semiconductor devices. A complex Fourier series approach is used to predict to terminal voltage and current waveforms. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6160